Social support and their relationship to the quality of life of students of the College Education for Women (Journal of the College of Education for Women, 2019)
The study is aimed at social support to the students of the College of Education for women (The research sample) and measuring the quality of life at students of the College of Education for women (The research sample) And to identify the relationship between social support and quality of life of students of the College Education for Women and research sample consisted of 200 students The adoption of the resolution as a tool for data collection and the most important results of the search results that the students of the College Education for Women have social support. In other words, parents and friends are supporting the students. The students have the quality of life any positive meaning to life and that when a person has a quality of life be guided positively toward him social support and it helps and there are goals for life And statistical processing signals to the existence of a positive correlation between positive social support and quality of life and relationship researchers made a number of recommendation.